Teaching Reading Comprehension through Story Mapping Technique at Senior High School in North Luwu - Husnaini bin Pekko (Universitas PGRI Yogyakarta, 2021)
AbstractThe purpose of this research was to find out whether the use of story mapping technique is effective or not in improving students’ reading comprehension on the narrative text at Senior High Schools in Luwu Utara. This research applied pre-experimental design. The population of this research was the tenth grade students SMAN 3 Luwu Utara. The samples of this research were 10 students. The sampling technique in this research was purposive sampling. The instrument of this research was reading test of narrative texts. The researcher gave pretest and posttest to the students. SPSS 20 was used to analyze the data. The result of this research showed that the use of story mapping technique in in improving students’ reading comprehension is effective. It proved by the result of the data indicated that there was a significant difference between the pre-test and post-test. The mean score in the pre-test was 47.80 and the mean score in the post-test was 81.40. The value of t0 (ttest) = 8.297, the value of tt (ttable) = 2.262 at the level of significance is 5% (0,05) with degree of freedom (df) = 9. Based on the result namely 8.297> 2,262 or t0 (ttest) was higher than tt (ttable), t0 > tt, it means that the story mapping technique is effective in improving students’ reading comprehension on the narrative text at Senior High School No. 3 in Luwu Utara. Key Words: Reading Comprehension, Narrative Text, Story Mapping Technique.